If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (7x + 3)(4x + -5) = 0 Reorder the terms: (3 + 7x)(4x + -5) = 0 Reorder the terms: (3 + 7x)(-5 + 4x) = 0 Multiply (3 + 7x) * (-5 + 4x) (3(-5 + 4x) + 7x * (-5 + 4x)) = 0 ((-5 * 3 + 4x * 3) + 7x * (-5 + 4x)) = 0 ((-15 + 12x) + 7x * (-5 + 4x)) = 0 (-15 + 12x + (-5 * 7x + 4x * 7x)) = 0 (-15 + 12x + (-35x + 28x2)) = 0 Combine like terms: 12x + -35x = -23x (-15 + -23x + 28x2) = 0 Solving -15 + -23x + 28x2 = 0 Solving for variable 'x'. Factor a trinomial. (-3 + -7x)(5 + -4x) = 0Subproblem 1
Set the factor '(-3 + -7x)' equal to zero and attempt to solve: Simplifying -3 + -7x = 0 Solving -3 + -7x = 0 Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -7x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -7x = 0 + 3 -7x = 0 + 3 Combine like terms: 0 + 3 = 3 -7x = 3 Divide each side by '-7'. x = -0.4285714286 Simplifying x = -0.4285714286Subproblem 2
Set the factor '(5 + -4x)' equal to zero and attempt to solve: Simplifying 5 + -4x = 0 Solving 5 + -4x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -4x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -4x = 0 + -5 -4x = 0 + -5 Combine like terms: 0 + -5 = -5 -4x = -5 Divide each side by '-4'. x = 1.25 Simplifying x = 1.25Solution
x = {-0.4285714286, 1.25}
| 100-c=129 | | 2d-4(d+6)=6d-48 | | (5a^2b-^3/10a-^2b-^4)^3 | | z/5-4=3/1/3 | | .15x+20=.10x+30 | | .10x+.25y=5.10 | | 9x18/5 | | 9.2x+50.82=-10.8x+50.10 | | (5a^2b-^3)/(10a-^2b-^4)^3 | | 9x+3=65 | | K+(4K+32)=32 | | 20-x/15=17 | | 4(2x-8)+6=26 | | 250000=5000{[(1.12)^n-1]/[.12]} | | 5w+10=15w | | 57x=45 | | 4(w-16)+2w=0 | | 4x=9x-9 | | 4m-7=1 | | 4x+ef=9x-9 | | 10p-4= | | 7(5/9)-9=4-2(5/9) | | 5(2m+9)=10(m+3)-40m | | -7t+2=16 | | 3.5d+9.75=6+4.75d | | n/-3=-16/3 | | 3-3r+5r=2r+2 | | z/5-7=1/5/6 | | N/6×6/1 | | -7.6(x-3.25)=30.4 | | 1+(4+a)=15 | | 3.6=7x |